2021
DOI: 10.1039/d0bm01903h
|View full text |Cite
|
Sign up to set email alerts
|

Single chain variable fragment fused to maltose binding protein: a modular nanocarrier platform for the targeted delivery of antitumorals

Abstract: A modular platform for targeted delivery was based on a single chain variable (ScFv) fragment fused to maltose-binding protein (MBP). Using different maltosylated ligands it is likely to target, transport drugs, or deliver genes to specific cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A co-expression system was used to produce a soluble fusion MBP-D16F7 scFv in E. coli. The scFv fragment was developed as a fusion protein MBP-scFv, which not only provides a more soluble and functional protein, but also can bind the scFv to the maltose on the surface of BioMOFs (Ca-Gly-Maltose) ( Reche-Perez et al, 2021 ). Our results showed that the synthesized BioMOFs were safe and nontoxic as empty carriers and that the unloaded Ca-Gly-D16F7 BioMOF had a stronger effect on cancer cells than on normal cells by inhibiting the proliferation of eukaryotic cells especially at a concentration greater than 100 μg/ml ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A co-expression system was used to produce a soluble fusion MBP-D16F7 scFv in E. coli. The scFv fragment was developed as a fusion protein MBP-scFv, which not only provides a more soluble and functional protein, but also can bind the scFv to the maltose on the surface of BioMOFs (Ca-Gly-Maltose) ( Reche-Perez et al, 2021 ). Our results showed that the synthesized BioMOFs were safe and nontoxic as empty carriers and that the unloaded Ca-Gly-D16F7 BioMOF had a stronger effect on cancer cells than on normal cells by inhibiting the proliferation of eukaryotic cells especially at a concentration greater than 100 μg/ml ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among existing expression systems, those based on E. coli have become popular for use in scFvs preparation, although use of an E. coli -based system to generate the two intrachain disulfide bonds necessary for antibody folding and antigen-binding activity can be challenging [ 20 ]. To address this problem, researchers have designed various strategies to produce functional scFvs by promoting their accumulation within the periplasm, where the oxidising environment supports disulfide bond formation and corrects scFv folding [ 20 , 37 , 42 45 ]. In this work, AK2 was expressed in soluble form in E. coli HB2151 cells after it was isolated from the scFv phage library.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having several advantages (e.g., high affinity and specificity toward their pertinent antigens), full-length antibodies are relatively large molecules (ranging 140-150 kDa). This drawback may limit their application when dealing with solid tumors [28, 29]. Long half-life and limited penetration of full-length antibodies can lead to high background levels, resulting in a low tumor-to-background ratio [3, 30].…”
Section: Introductionmentioning
confidence: 99%